Potential role of apolipoprotein B/A1 ration in obese and non-obese female patients of coronary artery disease - Mahto, Sunita; Sharma, Suman Bala; Dwivedi, Shridhar; Sethi, Mani; Saxena, Rahul (Asian Journal of Medical Sciences, 2016)
Background: Obesity and hyperlipidemia are considered to be risk factor for cardiovascular diseases. Many patients who develop coronary artery disease (CAD) are non obese and have normal lipoprotein cholesterol. Assessment of apolipoproteins can improve future risk of cardiovascular complications. Aims and Objectives: We have investigated effect of weight in relation with lipoprotein and apolipoprotein levels as efficient marker of CAD in North Indian females. Materials and Methods: The study population consist of 90 subjects categorized into three groups: Group I: Healthy controls; Group 2: Non obese patients of CAD and Group 3: Obese patients of CAD (n= 30 each group). Serum lipid profile along with apolipoprotein B and A1 were measured and apolipoprotein B/A1 ratio were calculated. Result: Total cholesterol and triglycerides levels were significantly high in obese patients as compared to non-obese and controls. LDL-C and HDL-C were altered insignificantly (p<0.1) in Group 2 and Group 3 as compared to Group 1. Apo B and apo A1 were significantly high in obese and non-obese CAD patients as compared to controls whereas insignificant difference was observed (p<0.1) when Group 3 patients were compared with Group 2. ApoB/Apo A1 ratio was increased significantly (p<0.01)) in patient groups as compared to controls. Conclusion: Although LDL-C and HDL-C were normal in subjects of CAD, increase in Apo B, A1 and its ratio authenticates the fact that these markers are more efficient in detection of CAD risk in obese and non obese patients than conventional lipid profile parameters. Asian Journal of Medical Sciences Vol. 7(3) 2016 18-22